Analisis Kelayakan dan Keberlanjutan Model Bisnis Hidroponik (Studi Kasus: AA Hidroponik Surakarta) - Rahmad Nur Sidiq; Setiyani, Rahmawati; Sepfrian, Bimoseno (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
The hydroponics business is showing strong growth trends, supported by high market demand and lucrative opportunities, especially amid increasing demand for fresh produce and awareness of food safety in regions with limited agricultural land such as the Surakarta Residency. The purpose of this study is to analyze the feasibility and sustainability of the hydroponic business model at AA Hydroponic, a growing business experiencing increased demand in Surakarta. The research method used is a case study at AA Hydroponic, conducted over a period of six months, from March to August 2025. Data collection was carried out through documentation, interviews, and direct observation with business actors. The main data analysis used a SWOT matrix to formulate business strategies and Efficiency Analysis to evaluate operational systems, particularly product distribution. The SWOT analysis results show that the business development of AA Hydroponic is on a healthy and positive trend, capable of utilizing its strengths to exploit opportunities. Furthermore, analysis of product distribution efficiency shows a value of 0.33 or 33%. This value indicates that the company is able to produce and distribute vegetables at a relatively low cost. The AA Hydroponics business model shows strong sustainability, driven by clear market segmentation (B2B and B2C) and healthy profit potential. Finally, this case study shows the potential for healthy profits, and with market maintenance and consistency, the sustainability of this hydroponic business model is very promising in the future.